Kontrol Struktur Geologi Terhadap Distribusi Manifestasi Panas Bumi di Daerah Subang dan Sekitarnya, Kabupaten Kuningan, Provinsi Jawa Barat. - Rastra, Rastra Yandra Satya Nugraha; Sutriyono, Edy; Gusti, Ugi Kurnia (Mataram University, 2025)
The influence of geological structures on the distribution of geothermal manifestations in the Subang area and its surroundings, Kuningan Regency, West Java Province, was assessed through an integrated approach combining lineament analysis based on Digital Elevation Model (DEM) imagery, fault and fracture density mapping, surface temperature analysis using Landsat 8 imagery, and surface geological surveys. The results indicate that three main hot spring points are closely associated with high-density fracture zones and active thrust fault systems. The primary geological structures controlling the system include the Ci Monte Fault and Situ Gede Fault, as well as the Ci Monte Syncline and Pamulihan Anticline, all trending east–west and formed due to compressive stress oriented north–south and northeast–southwest. These faults and fractures are strongly inferred to serve as migration pathways for hydrothermal fluids from the reservoir to the surface. The alignment of geothermal manifestations with geological structures highlights the critical role of active fractures and faults as the main controlling factors in the geothermal system. This conclusion underscores that geological structures function not only as natural permeable conduits but also as key indicators in geothermal exploration, especially in tectonically active regions.